Terror or Terrorism? Al-Qaeda and the Islamic State in Comparative Perspective - Gomes,Aureo de Toledo (2018)
The article compares al-Qaeda and ISIS, which despite similar origins have developed distinct paths and goals. According to our analytical framework, this is because al-Qaeda appears to use terror as a tool to induce other audiences into particular behaviors, expecting to change the correlation of forces in its favor in the future, while ISIS is a more complex organization whose primary goal is to build a new political order in territories it occupies. The results highlight the problems of treating both organizations as terrorist groups and contribute to debates on conceptually defining terrorism.